1978
DOI: 10.1346/ccmn.1978.0260203
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-Titanium-Bearing Mixed-Layered Clay from Potash Sulphur Springs, Arkansas

Abstract: Abstraet--A unique vanadium-titanium-bearing mixed-layered clay is currently being mined as an ore of vanadium at Potash Sulphur Springs, AR. The clay contains 80% expandable portion and has both a 14.22 and 18.24/~ hydration state in addition to the 9.49/~ dehydrated state; ethylene glycol expands this material to 16.69 A. The 060 reflection for all hydration states is between 1.50 and 1.51 ]k indicating the material is dioctahedral. The "mean chemical formula" calculates as (Cao.o8 Ko.o2 Nao.os)o.13 (A10.11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This analysis indicates that the clay is dominantly smectite (80%) with a small amount of mixed-layering. Overall the XRD results are similar to those obtained by McCormick (1978) for a sample from a vanadium deposit near the Potash Sulfur Springs intrusive complex, which is 7 miles west of the Christy deposit. McCormick concluded that the positions of the (001) reflections were not rational (Moore and Reynolds, 1989) as a result of a small amount of mixed-layering.…”
Section: Mineralogysupporting
confidence: 81%
“…This analysis indicates that the clay is dominantly smectite (80%) with a small amount of mixed-layering. Overall the XRD results are similar to those obtained by McCormick (1978) for a sample from a vanadium deposit near the Potash Sulfur Springs intrusive complex, which is 7 miles west of the Christy deposit. McCormick concluded that the positions of the (001) reflections were not rational (Moore and Reynolds, 1989) as a result of a small amount of mixed-layering.…”
Section: Mineralogysupporting
confidence: 81%
“…Clay minerals containing a substantial amount of vanadium have been described in various geologic environments: sedimentary (Foster, 1959;Hathaway, 1959;Guven and Hower, 1979;Whitney and Northrop, 1986;Parnell, 1988;Forbes, 1989;Hofman, 1990), metamorphic (Snetsinger, 1966;McCormick, 1978;Schade et al, 1986;Oh and Trichet, 1990;Pan and Fleet, 1992), and hydrothermal (Yoshimura and Momoi, 1964;Hofman, 1990;Johan and Povondra, 1987). In sandstones from the Colorado Plateau, vanadium clays are produced by the mineralization processes that form uranium deposits .…”
Section: Introductionmentioning
confidence: 99%
“…McCormick (1978) described a unique vanadium-titanium mixed-layer clay as the ore from this site. Milton (1978) was unable to confirm Mumpton (1965) and McCormick's (1978) hypothesis that hydrothermally precipitated montmorillonite-illite was the major ore mineral. Instead he discovered that an extremely fine-grained aggregate of complex mineralogy forming at least half of the rock (the gangue of the macroscopically observable vanadium minerals) may be the major vanadium carrier.…”
Section: Minerals Of the Vanadium Depositsmentioning
confidence: 96%